Konsep Desain Pengelolaan Dan Pemeliharaan Prasarana Ruang Jalan Umum Sesuai Standar Laik Fungsi Jalan Dan Standar Ruang Terbuka Hijau Kawasan Perkotaan - Suwardo Suwardo; Heru Budi Utomo (Penelitian dan Pengabdian Kepada Masyarakat Sekolah Vokasi Universitas Gadjah Mada, 2018)
The objectives of the research are (1) to identify the infrastructure of green open space (RTH) concept on the road corridor, (2) to analyze the fulfillment of road space conditions against the requirements of road functional (SLFJ), (3) to analyze the completeness and condition of the road facilities to meet the green open space standard (SRTH), and (4) to set up development directives and design concepts for the management and maintenance of road space infrastructures that support green open space standards based on road functional requirements. Primary data for the analysis were obtained by direct observation/survey at the research site in Jalan Abu Bakar Ali, Malioboro, and Solo in Yogyakarta City and survey of respondents of road users with questionnaires. Secondary data used to support the analysis are (a) road map and condition of around study sites, (b) assumptions in design standards, (c) standards on markers, signs, lighting, drainage, and (d) related study reports. The method of quantitative and qualitative analysis according to SLFJ and SRTH was applied rationally. It can be concluded that the knowledge and perceptions of respondents about the use of road space and environmental conditions around the road in the three locations was obtained in Good category with scores of 3.4; 3.52; and 4.2, respectively. In Jalan Abu Bakar Ali respondents responded Agreed (score of 4.18), meaning that it required additional facilities and maintenance of the RTH’s facilities and landscape. The management and maintenance of RTH's infrastructure and facilities of Jalan Abu Bakar Ali, Jalan Malioboro and Jalan Solo has been done by Yogyakarta City Planning Agency, organized and well-scheduled. Based on the evaluation of road functional requirement in Jalan Abu Bakar Ali (secondary collector), Jalan Malioboro (secondary artery), and Jalan Solo (secondary artery), all that are categorized as Conditional Function (LS). It means that the road has not fulfilled some road functional requirements in terms of utilization of road space, or there are still technical recommendations that must be met so that roads can be categorized as Function (LF). It obtained that Road Use Space (RUMAJA) is not effectively used, which characterized by still many permanent and non permanent buildings in the RUMAJA area. The design concept of the management and maintenance of road infrastructure should be based on the principle of maximizing road function (according to SLFJ) and the fulfillment of green open spaces on sidewalks and around (according to SRTH).